The Role of miR-31-5p in the Development of Intervertebral Disc Degeneration and Its Therapeutic Potential - Zhou, Yong; Deng, Mingsi; Su, Jiqing; Zhang, Wei; Liu, Dongbiao; Wang, Zhengguang (Frontiers in Cell and Developmental Biology, 2021)
Intervertebral disc degeneration (IDD) refers to the abnormal response of cell-mediated progressive structural failure. In order to understand the molecular mechanism of the maintenance and destruction of the intervertebral disc, new IDD treatment methods are developed. Here, we first analyzed the key regulators of IDD through miRNA microarrays. The cell structure and morphology were discovered by Histological and radiographic. Then, the level of miR-31-5p was disclosed by qRT-PCR. The association between miR-31-5p and SDF-1/CXCR7 axis was discovered by 3′-Untranslated region (UTR) cloning and luciferase assay. The apoptosis of cells under different treatments was disclosed by Flow cytometer. The cell proliferation was discovered by EdU assay. Finally, the protein levels of SDF-1, CXCR7, ADAMTS-5, Col II, Aggrecan and MMP13 were discovered by Western blot. The results show that miR-31-5p is a key regulator of IDD and its level is down-regulated in IDD. Overexpression of miR-31-5p facilitates NP cell proliferation, inhibits apoptosis, facilitates ECM formation and inhibits the level of matrix degrading enzymes in NP cells. The SDF-1/CXCR7 axis is the direct target of miR-31-5p. miR-31-5p acts on IDD by regulating SDF-1/CXCR7. In vitro experiments further verified that the up-regulation of miR-31-5p prevented the development of IDD. In conclusion, overexpression of miR-31-5p can inhibit IDD by regulating SDF-1/CXCR7.